Ethnicity and anthropometric deficits in children: A cross-sectional analysis of national survey data from 18 countries in sub-Saharan Africa. - Lucy S Tusting; Swapnil Mishra; Harry S Gibson; Steven W Lindsay; Daniel J Weiss; Seth Flaxman; Samir Bhatt (PLOS Global Public Health)
Child anthropometric deficits remain a major public health problem in Sub-Saharan Africa (SSA) and are a key target of the UN Sustainable Development Goals (SDGs). The SDGs recommend disaggregation of health indicators by ethnic group. However, few studies have assessed how ethnicity is associated with anthropometric deficits across SSA. Data were extracted from 37 georeferenced Demographic and Health Surveys carried out during 2006-2019 across SSA that recorded anthropometric data for children aged <5 years. In a cross-sectional analysis, the odds of stunting (low height-for-age), wasting (low weight-for-height) and underweight (low weight-for-age) were modelled in relation to ethnic group using a generalised linear hierarchical mixed-effects model, controlling for survey design and environmental, socioeconomic and clinical variables. The study population comprised 138,312 children spanning 45 ethnic groups across 18 countries. In pairwise comparisons (accounting for multiple comparisons) between ethnic groups, height-for-age z-scores differed by at least 0.5 standard deviations in 29% of comparisons, weight-for-height z-scores in 36% of comparisons and weight-for-age z-scores in 20% of comparisons. Compared to a reference group of Fula children (the largest ethnic group), ethnic group membership was associated with both increases and decreases in growth faltering, ranging from a 69% reduction to a 32% increase in odds of stunting (Igbo: adjusted odds ratio (aOR) 0.31, 95% confidence intervals (CI) 0.27-0.35, p<0.0001; Hausa: aOR 1.32, 95% CI 1.21-1.44, p<0.0001); a 13% to 87% reduction in odds of wasting (Mandinka: aOR 0.87, 95% CI 0.76-0.99, p = 0.034; Bamileke: aOR 0.13, 95% CI 0.05-0.32, p<0.0001) and an 85% reduction to 13% increase in odds of underweight (Bamileke: aOR 0.15, 95% CI 0.08-0.29, p<0.0001; Hausa: aOR 1.13, 95% CI 1.03-1.24, p = 0.010). Major ethnic disparities in stunting, wasting and underweight were observed across 18 countries in SSA. Understanding and accounting for these differences is essential to support progress monitoring and targeting of nutrition interventions in children.